Sarcopenia in older patients with osteoarthritis of large joints - Yu. A. Safonova; E. G. Zotkin (Научно-практическая ревматология)
Pathological changes of large joints (knee, hip) in osteoarthritis (OA) are accompanied by the development of muscle weakness, decreased proprioception and imbalance.Objective: assessment of skeletal muscles state in women over 65 years old with OA of large joints and determination of the main factors affecting the risk of sarcopenia.Subjects and methods. In 159 women with OA (mean age 74±6 years), muscle mass was assessed with the appendicular lean mass index (ALM) using dual-energy X-ray absorptiometry (DXA). Muscle strength was measured by hand dynamometer, muscle function was determined by the results of a brief set of physical activity tests (short physical performance battery – SPP). The quality of life was analyzed by the EQ-5D questionnaire, pain assessment was carried out using a visual analog scale (VAS).Results and discussion. Patients with sarcopenia were significantly more likely to have lower rates of ALM index (p<0.001), body mass index (p<0.001) and muscle strength (p<0.01). The incidence of sarcopenia increased with age (p<0.01). Muscle function measures are reduced in women with OA, regardless of the presence of sarcopenia. Falls in the previous 12 months before inclusion in the study in patients with sarcopenia were observed significantly more often than without sarcopenia: in 90 and 24.8% of cases (95% CI 78.2–96.7 and 17.0–34.0, respectively p<0.001). Clinically expressed pain in large joints in patients with and without sarcopenia was found with the same frequency. The average value of the EQ-5D index in women with sarcopenia was significantly less than without sarcopenia (0.48±0.22 and 0.74±0.27 respectively), mainly due to a decrease of the usual daily activities (p<0.01). However, in women over 85 years of age, the quality of life was comparable regardless of the presence or absence of sarcopenia.